International retailing - Alexander, Nicholas (Blackwell Business, 1997)
In recent years interest in international retailing has grown considerably as retailers' activities have become increasingly international. The first single-authored text to be published in this area of growing importance, International Retailing will be of particular value to students of retailing, marketing and international business. International Retailing moves from a definition of the subject to consider the models which have been developed to interpret it. The book provides students with a firm theoretical basis upon which to understand international retailing activity and illustrates it by reference to international retailing practice and experience. All aspects of retailing are covered from an international perspective and supported by a full range of international examples and cases. Self-contained illustrations of international retail experiences are used to focus the reader's attention on aspects of the international retail environment and the specific experiences of international retailers. Filled with examples from real businesses, discussion questions, topic summaries and cases, this text will be essential reading for all students of international retailing.